Centroid⋯centroid and hydrogen bond interactions as robust supramolecular units for crystal engineering: X-ray crystallographic, computational and urease inhibitory investigations of 1, 2, 4-triazolo[3, 4-a]phthalazines. Issue 29 (7th July 2022) - Zaib, Sumera; Ibrar, Aliya; Ramay, Marriyam; Zahra, Shabab; Hökelek, Tuncer; Simpson, Jim; McAdam, Christopher John; Awwad, Nasser S.; Ibrahium, Hala A.; Frontera, Antonio; Khan, Imtiaz
Abstract : The antiparallel π-stacked dimer of compound 6 (left) presenting a large dimerization energy (Δ E 5 = −11.2 kcal mol −1 ) and confirming its relevance in the solid state of compound 6 . 3D binding mode of 6 (right) docked in the catalytic domain of urease. Abstract : Recognizing the conspicuous role of organic molecular crystals in pharmaceutical industry, we herein report the crystal engineering of two readily accessible 1, 2, 4-triazolo[3, 4- a ]phthalazine compounds (5 and 6 ) involving noncovalent interactions namely hydrogen bonding and aromatic interactions. The synthesis of both compounds was achieved via a facile multi-step protocol in good yield and structures were established using NMR spectroscopy and X-ray crystallographic analysis. The supramolecular assembly of phthalazine derivatives showed a dominated network of hydrogen bonding (C–H⋯N, C–H⋯Cl) and π⋯π interactions. The nature and strength of noncovalent interactions were further visualized using Hirshfeld molecular surface analysis, crystal voids, intermolecular interaction energies and energy frameworks. The structure-directing character of these interactions was confirmed theoretically by density functional theory calculations including molecular electrostatic potential (MEP) surfaces, atoms-in-molecules analysis and NCI plot computational tools. The medicinal potential of phthalazines 5 and 6 was assessed against urease enzyme where compound 6 displayed a remarkable inhibition profile with an IC50 value of 0.32 ± 0.02 μM, ∼70-fold higher activity compared to thiourea (standard inhibitor). Molecular docking analysis of both compounds revealed several vital interactions with key amino acid residues inside the active pocket of urease whereas kinetics studies depicted the competitive mode of compound 6 . Furthermore, HYDE assessment and SeeSAR analysis revealed that both compounds show significant docking scores with effective binding affinities. The molecular dynamics simulations were also performed for compound 6 and the results suggested the stability of compound 6 + protein complex over 30 ns time period. Finally, pharmacokinetic properties predicted the drug-likeness and blood–brain barrier permeation of the tested compounds.